2023
DOI: 10.1097/ta.0000000000004064
|View full text |Cite
|
Sign up to set email alerts
|

Titratable partial aortic occlusion: Extending Zone I endovascular occlusion times

Abstract: Background Extending the time to definitive hemorrhage control in non-compressible torso hemorrhage (NCTH) is of particular importance in the battlefield where transfer times are prolonged and NCTH remains the leading cause of death. While REBOA is widely practiced as an initial adjunct for the management of NCTH, concerns for ischemic complications after 30 minutes of compete aortic occlusion deters many from Zone 1 deployment. We hypothesize that extended zone 1 occlusion times will be enabled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Despite limited clinical evidence for pREBOA, 34 35 48 studies by Matsumura et al 48 and others show promising outcomes. Matsumura et al demonstrated that patients undergoing pREBOA had better hemodynamic responses and longer occlusion time compared with conventional REBOA (median 58 minutes vs. 33 minutes), with comparable mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite limited clinical evidence for pREBOA, 34 35 48 studies by Matsumura et al 48 and others show promising outcomes. Matsumura et al demonstrated that patients undergoing pREBOA had better hemodynamic responses and longer occlusion time compared with conventional REBOA (median 58 minutes vs. 33 minutes), with comparable mortality.…”
Section: Resultsmentioning
confidence: 99%
“… 38 52–55 The pREBOA-PRO device enables longer zone 1 deployment without frequent adjustments, improving outcomes. 34 38 Its dual arterial line capability allows real-time monitoring of central aortic and distal femoral artery pressures, providing evidence of ongoing perfusion and guiding resuscitation. 34 In a clinical setting, the use of pREBOA-PRO devices allowed longer zone 1 total occlusion times without worsening distal ischemic injury compared with complete occlusion devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated the safety of Zone 1 partial occlusion for extended periods, but the majority of patients from this study suffered blunt injuries, and injury patterns were not included. 3 In our case, we present a patient with a life-threatening penetrating liver injury that was successfully managed non-operatively by leveraging PBAO. A 46-year-old male suffered gunshot wounds (GSW) to the epigastrium, right flank, right shoulder, and back.…”
mentioning
confidence: 99%
“…Utilizing REBOA for partial aortic occlusion (PBAO) has gained attention over the past several years because PBAO affords improvement in central blood pressure while minimizing the amount and duration of distal ischemia. 2,3 Partial aortic occlusion allows the provider to make targeted changes in volume and thus titrate the amount of aortic occlusion, and thereby the amount of blood flow distally. This may provide more time to mobilize resources for definitive hemorrhage control while minimizing the morbidity of ischemia.…”
mentioning
confidence: 99%